2013
DOI: 10.1111/jnu.12056
|View full text |Cite
|
Sign up to set email alerts
|

Israeli Nurses’ Intention to Report for Work in an Emergency or Disaster

Abstract: This study makes an important contribution to research on the importance of perceived self-efficacy in the context of disaster planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 40 publications
12
62
0
2
Order By: Relevance
“…Moreover in our previous study, conducted in Israel, we found that perceived knowledge, personal risk appraisal and self‐efficacy in emergency functioning were important considerations in nurses’ intention to report for work (Melnikov et al. ). Despite this extended research, the impact of several variables on the intention to report for work during an emergency remained unexplained.…”
Section: Introductionmentioning
confidence: 92%
“…Moreover in our previous study, conducted in Israel, we found that perceived knowledge, personal risk appraisal and self‐efficacy in emergency functioning were important considerations in nurses’ intention to report for work (Melnikov et al. ). Despite this extended research, the impact of several variables on the intention to report for work during an emergency remained unexplained.…”
Section: Introductionmentioning
confidence: 92%
“…Another survey of primary care health staff in Guangdong Province, China found that only one-fourth of respondents had participated in emergency response in the past, reflecting both poor response capacity and lack of experience [11]. In a survey of Israeli nurses, less than half had reported to work when asked in the past year following a response [12]. Another Israeli survey indicated that only 51% of hospital workers said they would report following a missile attack [13].…”
Section: Introductionmentioning
confidence: 99%
“…[5] The literature review of this study revealed that, although nurses seem to be unprepared to respond to disasters, they are willing to undertake training to improve their preparedness. [9,10,16,18,21,22,24,[33][34][35] Thus, the current study examined the disaster preparedness of emergency nurses working in health services in the KSA.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies agree that nurses are poorly prepared for disasters by their planning, education, training and responses. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Nurses must know the relevant disaster emergency plan to be familiar with and recognise their role when an event requires them to respond. [9,10,14,16,24] A clear disaster plan will inform nurses of their chain of command.…”
Section: Introductionmentioning
confidence: 99%